Trilogía de la arquitectura peruana - Beingolea Del Carpio, José (2025)
The trilogy built between 2014 and 2024 assumes a maximalist theoretical basis: coloniality as a structural condition, its influence on architecture understood as a historically determined concept and as a system, therefore, beyond the object itself, and which applies it to Peruvian architecture represented by a well-conceived sample: the star architect from Lima, the manifestations of architectural otherness and a selection of non-popular architecture.